Digital occlusal contact area indicates masticatory performance for normal occlusion, but not for malocclusion - Vortkamp, Paulina; Rues, Stefan; Räther, Sven; Eberhard, Lydia; Rößler, Alexander Fritz; Bouffleur, Frederic; Kühle, Reinald; Schwindling, Franz Sebastian; Rammelsberg, Peter; Roser, Christoph; Herpel, Christopher (Journal of oral rehabilitation, 2025)
Objectives Since 1949, occlusal contact area (OCA) has been recognised as an indicator of masticatory performance (MP), but it required individual and laborious analog measurement. Today, a digital workflow could provide automatic quantification. Objective To find optimal parameters for a digital evaluation in terms of maximising correlation between OCA and MP. Methods MP was measured clinically by comminution of standardised test food by 41 participants (mean age = 29, n female = 28), including 18 patients with dentofacial deformities and 23 healthy subjects with normal occlusion. OCA was measured in the laboratory. After impression taking, gypsum casts were digitised (D2000, 3shape) and aligned in maximum intercuspidation (Geomagic Design X2022, 3D Systems). The maxilla was enlarged with surface offsets of 100, 150, 200, 250, 300, 350, 400, 800 and 2000 μm to simulate different interocclusal distances. OCA was identified at the mandible surface by intersection with the respective enlarged maxilla scan (3D surface area). OCA projection onto the occlusal plane (2D area) was also computed, resulting in a total of 18 different OCA evaluations per patient. Results MP was lower in patients with malocclusion than in individuals with normal occlusion (X50 mean 5.35 vs. 4.62). The 18 mean OCAs ranged from 11 to 852 mm2. In subjects with normal occlusion, strong correlations were shown for interocclusal distances between 150 and 300 μm combined with 3D projection (r < −0.7). For patients with malocclusion, no significant correlations were identified. Conclusions OCA appears a suitable indicator of MP in individuals with normal occlusion, but not in patients with malocclusion, where other factors seem more determinant.
Online verfügbar: 04. Mai 2025
Gesehen am 16.10.2025